Synchronous and antecedent malignancies in patients with papillary thyroid carcinoma - Çelik, Mehmet; Yılmaz Bülbül, Buket; Aytürk, Semra; Küçükarda, Ahmet; Taştekin, Ebru; Can, Nuray; Üstün, Funda; Sezer, Yavuz Atakan; Güldiken, Sibel (The European Research Journal, 2018)
Objective. This study aimed to evaluate concurrently detected second primary malignancy in the patients who underwent surgery for papillary thyroid carcinoma. Methods. In this study, we retrospectively analyzed the files of the patients who underwent surgery for papillary thyroid carcinoma between 2000-2017. A total number of 601 patients with papillary thyroid carcinoma were evaluated. Among these patients, 48 patients were found to have secondary primary tumors. Preoperative and postoperative laboratory examination findings of the patients were retrospectively recorded. Results. Among 601 patients with papillary thyroid cancer evaluated with respect to radiation exposure, the second primary tumor with breast cancer was found to be the most common tumor. Renal cell carcinoma, malignant melanoma and stomach cancer were found to be more frequent when evaluated regardless of radiation effect. Furthermore, when molecular genetic results were evaluated, BRAF mutation rate was found to be more frequent than in other secondary tumors, especially in patients with renal cell carcinoma. Conclusions. The importance of epidemiological and experimental studies of multiple cancers is obvious. Although it is known that the impact of radiation is considerable among the ones with concurrence of breast cancer and papillary thyroid carcinoma, we suggest that further studies on common molecular genetic characteristics and development of targeted treatment for detected molecules are required in the patients with renal cell carcinoma in whom papillary thyroid carcinoma is diagnosed regardless of radiation effect.